La mort de la gazelle . The Death of the Gazelle - Reichenbach, Jeremie (Entre2prises, 2009)
Verzio FF Submission Since the late 1980s, a sporadic and bloody guerrilla war has plagued Niger. In February 2007, a group of armed men claiming to be from the Nigerians’ Movement for Justice attacked an army barracks. One year later, hundreds have joined up with the MMJ hiding in the mountains. A film about men isolated by the world, waiting to wage war against an invisible enemy, with one common question in mind: when will the fight start?